Developing Web-based Practical Procedure Guidance for Social Rehabilitation in The Society 5.0 Era - Naufal Libna Dawiya; Nenden Rani Rinekasari; Yani Achdiani (JIPTEK : Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2022)
This research was based on issues related to Society 5.0 era for the requisite learning process to be linked to technology. The technology can provide students with flexible time to access learning materials. In addition, the specification of the material in this research is a practical social rehabilitation procedure for handling sexual assault for adolescents. This research aims to develop web-based practice guidance for the practical procedure of social rehabilitation in the society 5.0 era. The research was carried out to produce guidance for the practical procedure products that can be used for practical application in lectures to facilitate students' ability to practice social rehabilitation after graduating. This study uses the Research and Development (R&D) method with the Planning, Production, and Evaluation (PPE) model. The research process involves documentation studies and validity tests by two media experts. The study results prove that the web-based guidance for the practical procedure is valid to be used as a resource for learning practical procedures in the Social Rehabilitation course. These results are based on the experts' assessment, with an average rating from the two media experts being 86.59% in the "Valid (Not Revised)" category. This research produces web-based practice guidance for the practical procedure of social rehabilitation, which has been assessed through expert judgment and proven valid to be applied by the lecturer of Social Rehabilitation courses at the Family Welfare Education Universitas Pendidikan Indonesia (FWE UPI) Study Program.